KOMUNIKASI ANTARPRIBADI ANTAR KARYAWAN DALAM MENINGKATKAN KUALITAS KERJA DIVISI HUMAS PT PERKEBUNAN NUSANTARA V PEKANBARU - Eni Karlina Siregar; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Interpersonal communication between employees will determine the quality of work of employees and is the key to the success of employee performance. Employees of the Public Relations Division of PT Pekebunan Nusantara V Pekanbaru have very close relations and family relationships. Communication that takes place harmoniously and openly, but with this, misunderstandings on public relations employees still occur so that it has an impact on the quality of work of the Public Relations Division of PT Perkbunan Nusantara V Pekanbaru. The theory used in this study is the theory of social penetration and the concept of Devito. The purpose of this study was to determine the relationship between employees in improving the quality of work, openness among employees in improving the quality of work, empathy among employees in improving work quality, supportive attitude among employees in improving work quality, positive attitude among employees in improving work quality, and equality among employees in improving the quality of work of the Public Relations Division of PT Perkebunan Nusantara V Pekanbaru. This study uses a type of qualitative descriptive research. Determination of informants using purposive techniques. Data collection techniques in this study are interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman analysis models for the validity of data checking techniques using data source triangulation and method triangulation. The results of this study indicate that, interpersonal communication between employees of the Public Relations Division of PT Perkebunan Nusantara V Pekanbaru runs well in improving the quality of work of the Public Relations Division of PT Perkebunan Nusantara V Pekanbaru. Relations between employees are harmonious and kinship, openness between employees in two forms, namely job openness and family openness, empathy among employees is to feel what employees feel, pay attention to fellow employees, high level of care, respect for employee work, supportive attitude between employees and forms of motivation, unselfish employees, collaboration between employees, positive attitudes among employees respecting employees, positive thinking among employees, believing in the importance of fellow employees and equality between employees equal position, familiar atmosphere of communication, and knowing the quality of work of employee. Keywords :  Employees, Interpersonal Communication, Quality of Work